Hydrothermal Steel Slag Valorization—Part II: Hydrogen and Nano-Magnetite Production - Crouzet, Camille; Brunet, Fabrice; Recham, Nadir; Auzende, Anne-Line; Findling, Nathaniel; Magnin, Valérie; Ferrasse, Jean-Henry; Goffé, Bruno (Frontiers in Earth Science, 2017)
The effect of acidic conditions (in a pH range of 3 to 6) and temperature on the kinetics of the hydrothermal oxidation of ferrous iron contained in BOF steel slag has been tested in the 150 – 350°C range for acid acetic concentrations from 0 to 4M. Reaction progress was monitored with the amount of produced H2. Higher temperature and lower pH are found to enhance the hydrothermal oxidation kinetics of the slag. These two parameters are believed to increase iron dissolution rate which has already been identified as the rate limiting step of the hydrothermal oxidation of pure FeO. An activation energy of 28  4 kJ/mole is found for the hydrothermal oxidation of the steel slag which compares very well with that of pure FeO under similar conditions. In the case of the slag run in water at 300°C for 70.5 hours, magnetite product has been separated magnetically and characterized. Particles were found to fall in three size ranges: 10 – 30 nm, 100 – 300 nm and 1 – 10 µm. The smallest fraction (10 – 30 nm) is comparable to the 10 – 20 nm size range that is achieved when nanomagnetite are synthesized by co-precipitation methods. Obviously, the production of nanomagnetite enhances the economic interest of the hydrothermal processing of steel slags, which has already proven its capacity to produce high-purity H2.